2015
DOI: 10.1155/2015/764163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Common Polymorphisms rs2910164 in miR-146a and rs11614913 in miR-196a2 on Gastric Cancer Susceptibility

Abstract: Background. Single nucleotide polymorphisms (SNPs) in genes encoding microRNAs may play important role in the development of gastric cancer. It has been reported that common SNPs rs2910164 in miR-146a and rs11614913 in miR-196a2 are associated with susceptibility to gastric cancer. The published results remain inconclusive or even controversial. A meta-analysis was conducted to quantitatively assess potential association between the two common SNPs and gastric cancer risk. Methods. A comprehensive literature s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Our results indicate that both polymorphisms are significantly associated with increased HCC risk. In line with other studies, the miR-146a rs2910164 and miR-196a-2 rs11614913 polymorphisms are associated with increased risk for other cancers like colorectal cancer ( Xu & Tang, 2015 ) and gastric cancer ( Ni et al, 2015 ) in the Asian population. The increased risk estimates found in our analysis are somewhat modest (OR < 1.6).…”
Section: Discussionsupporting
confidence: 88%
“…Our results indicate that both polymorphisms are significantly associated with increased HCC risk. In line with other studies, the miR-146a rs2910164 and miR-196a-2 rs11614913 polymorphisms are associated with increased risk for other cancers like colorectal cancer ( Xu & Tang, 2015 ) and gastric cancer ( Ni et al, 2015 ) in the Asian population. The increased risk estimates found in our analysis are somewhat modest (OR < 1.6).…”
Section: Discussionsupporting
confidence: 88%
“…29 In a study on the Asian population, It was shown that, the mir196a2 rs11614913 polymorphism seems to contribute to susceptibility to lung cancer risk, diagnosis, screening and therapy. 25,27 In several recent meta-analysis studies, it was found that there is no significant relationship between gastric cancer and mir169a2polymorphism, but in case-control studies in the Egyptian, German and Japanese populations, there was a significant correlation between mir196a2 rs11614913 polymorphism and stomach cancer prognosis. 27 By Comparing other extensive association studies that have been conducted in Asian and European populations with different techniques such as PCR RFLP, Taq man SNP Genotyping and DNA sequencing, on various types of cancer, it confirmed that mir196a2 rs11614913 polymorphism significantly increases the risk of breast and the lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…24 Moreover, miR155 has been characterized as a component of the primary macrophage response to different types of inflammatory mediators such as IFN-β or Tumor Necrosis Factor-α (TNF-α). [25][26][27][28][29] It has been shown that miR155 is induced by bacterial lipopolysaccharide (LPS) in a human monocytic cell line. 30 Some study in Egyptian population proposed that mir196a2 rs11614913 polymorphism could be associated with asthma severity.…”
Section: Introductionmentioning
confidence: 99%
“…Rs11614913 (T>C) is a common variant in pre-miR-196a2 that plays a role in the development of multiple cancer types, including gastric cancer (Peng et al, 2014;Ni et al, 2015;Nikolić et al, 2015;Qi et al, 2015;Wu et al, 2015). Several studies have evaluated the effect of this polymorphism on gastric cancer risk in different populations, but the results are inconsistent.…”
Section: Introductionmentioning
confidence: 99%